Failure evaluation on a high-strength alloy SA213-T91 super heater tube of a power generation - Ahmad J.; Purbolaksono J.; Beng L.C.; Ahmad A. (SAGE Publications Ltd, 2023)
This article presents failure investigation on a high-strength alloy SA213-T91 super-heater tube. This failure is the first occurrence involving the material in Kapar Power Station Malaysia. The investigation includes visual inspections, hardness measurements, and microscopic examinations. The failed super-heater tube shows a wide open rupture with thin and blunt edges. Hardness readings on all the as-received tubes are used for estimating the operating metal temperature of the super-heater tubes. Microstructures of the failed tube show numerous creep cavities consisting of individual pores and chain of pores which form micro- and macro-cracks. The findings confirmed that the super-heater tube is failed by short-term overheating. Higher temperatures of the flue gas due to the inconsistent feeding of pulverized fuels into the burner is identified to cause overheating of the failed tube.